A contemporary pedagogy of drawing. (2nd October 2021) - Riley, Howard
ABSTRACT: This article reviews 20 years of attitudes to drawing pedagogy and looks forward with a studioful of post-pandemic optimism. It reiterates the importance of drawing in art schools as the most direct and economic means of nurturing our intelligence of seeing . Throughout the period, neoliberal policies directing the UK higher education curricula towards market-oriented criteria of success have eroded the foundation of a visual arts pedagogy: the exploration of the perceptual and its communication through visual language; educative activities of wider import than market concerns. An articulacy in drawing – visualcy – is fundamental to human culture, let alone preparation for professional practice in the visual arts and design disciplines. A remedial pedagogy is proposed, structured upon the two fundamental theoretical bases of visual perception and visual communication, illustrated with students' drawings and the author's efforts to practise what he preaches.